Core i7: A Research into the Processor - Parkar, Erum; Khan, Naushin (International Journal of Computer Sciences and Engineering, 2019)
In late 2008, Intel launched the core i7 processor. This processor was made as an intention to target business and markets for laptops and computers. This processor was made mainly for gaming, intensively graphics tasks etc. This processor can handle a wide variety of tasks at once and hence are best suited for those who wants a computer with powerful performance. For data crunching, this processor is the most suitable. It has a fast clock speed and integrate max 4 cores. It also has Virtualization Technology and Streaming SIMD Instructions. It also supports Intel Turbo Boost technology.